Efektivitas Pembelajaran Daring dengan Menggunakan Model RMS Mata Pelajaran Sejarah - Sudibyo, Sigit; Kurniawati, Kurniawati (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2023)
The background of writing this article is the lack of understanding of the concepts and cognitive abilities of students in learning history. Social studies subjects at SMA N 102 Jakarta use the RMS learning model. The research method used is descriptive qualitative with a data analysis approach using the Miles and Huberman model. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that online learning using the RMS model in history subjects at SMAN 102 Jakarta is running effectively. In carrying out online learning the teacher uses the Google Classroom application, WhatsApp, and Zoom Meeting. Obstacles to learning to be brave for students, but some students stated that they did not like learning to be brave because some students felt that learning to be brave was not as ideal as face-to-face learning at school (enchanting learning). The assumption, most students think that there are not many drawbacks to using the RMS model for online learning in history classes, and it is easier for students to understand the material provided by the teacher.Latar belakang penulisan artikel ini adalah kurangnya pemahaman konsep dan kemampuan kognitif siswa dalam pembelajaran sejarah. Mata pelajaran IPS di SMA N 102 Jakarta menggunakan model pembelajaran RMS. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan analisis data menggunakan model Miles dan Huberman. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa pembelajaran online menggunakan model RMS pada mata pelajaran sejarah di SMAN 102 Jakarta berjalan efektiv. Dalam pelaksanaan pembelajaran online guru menggunakan aplikasi Google Classroom, WhatsApp, Zoom Meating. Hambatan pembelajaran daring bagi siswa, namun sebagian siswa menyatakan tidak menyukai pembelajaran daring karena sebagian siswa merasa pembelajaran daring tidak seideal pembelajaran tatap muka di sekolah (pembelajaran luring). Singkatnya, sebagian besar siswa berpendapat bahwa tidak banyak kekurangan dalam menggunakan model RMS untuk pembelajaran online di kelas sejarah, dan lebih mudah bagi siswa untuk memahami materi yang diberikan oleh guru.